Pengembangan E-Book Pembelajaran Kreatif Materi Analisis Kompleks untuk Peserta Didik Semester V - FX. Didik Purwosetiyono; M. Saifuddin Zuhri; Theodora Indriati Wardani; Maya Rini Rubowo (Perkumpulan Kualitama Edukatika Indonesia, 2023)
The aim of the research was to find out how the development of e-book media for creative learning of complex analysis material for students in the fifth semester of Mathematics Education students at PGRI Semarang University was feasible according to expert judgment, knowing the development of e-books for creative learning of complex analysis material for practical fifth semester students used in learning and knowing effective e-book learning creative learning on complex analysis material in fifth semester students in Mathematics Education students at PGRI University Semarang. Research development using the 4-D Thiagarajan model. The defining and planning stages were carried out so that draft I was obtained. Then at the development stage validation was carried out by two experts/experts using the learning tool validation sheet, so that suggestions were obtained to revise draft I to draft II so that it was feasible and could be used in learning. Furthermore, a limited trial was carried out to obtain input that was used to revise draft II to draft III. The research instrument is a test instrument. From the development of creative learning e-books on complex analysis material it was declared feasible, and from data analysis using the right-sided t test, it was found that learning outcomes using creative e-books on complex analysis material for fifth semester students were better than conventional classes.